2012
DOI: 10.1073/pnas.1201613109
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging of DNA curtains reveals mechanisms of KOPS sequence targeting by the DNA translocase FtsK

Abstract: FtsK is a hexameric DNA translocase that participates in the final stages of bacterial chromosome segregation. Here we investigate the DNA-binding and translocation activities of FtsK in real time by imaging fluorescently tagged proteins on nanofabricated curtains of DNA. We show that FtsK preferentially loads at 8-bp KOPS (FtsK Orienting Polar Sequences) sites and that loading is enhanced in the presence of ADP. We also demonstrate that FtsK locates KOPS through a mechanism that does not involve extensive 1D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 31 publications
6
79
1
Order By: Relevance
“…For experiments at a higher ionic strength, the NaCl concentration was increased to 130 mM. Human or yeast Exo1-biotin was prelabeled with streptavidin QDs (Qdot 705; Life Tech) before use, as previously described (72). To make the DNA curtain, λ-DNA was hybridized with a biotinylated oligonucleotide on one end and a 3′ overhang-generating oligonucleotide on the other end (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…For experiments at a higher ionic strength, the NaCl concentration was increased to 130 mM. Human or yeast Exo1-biotin was prelabeled with streptavidin QDs (Qdot 705; Life Tech) before use, as previously described (72). To make the DNA curtain, λ-DNA was hybridized with a biotinylated oligonucleotide on one end and a 3′ overhang-generating oligonucleotide on the other end (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to consider that when the ATPase subunits were fused into a concatemer, there might have been unknown and unintended alterations either to the ATPase activity of individual monomers or to their ability to form higher-order multimers, which could mask the effect of mutant subunits. Conversely, a number of single-molecule studies have now shown that the linked trimeric FtsK proteins appear to translocate and respond to nucleotides similarly to unlinked hexamers (77,179). Nevertheless, in order to explain these results, a new model in which more than one subunit within a hexameric ring would contact DNA concurrently was proposed.…”
Section: Fig 18mentioning
confidence: 99%
“…This ensures that the motor is loaded correctly onto DNA in a specific orientation and that the subsequent translocation is toward the XerCD-dif site. Directional translocation of DNA is, therefore, sequence dependent at the motor-loading step; further, a translocating FtsK appears to ignore additional KOPS and reads through them (77,84).…”
Section: Revolution Motorsmentioning
confidence: 99%
“…However, FtsK C stops at least transiently and/or dissociates at XerCD bound to dif (27,32). Reversals in translocation direction have been observed to occur spontaneously (18,28,30,31) and in response to XerCD bound to dif (32). The use of a fluorophore label, along with singly tethered DNA, has allowed us to observe FtsK C without requiring any loop extrusion, and to observe its interaction with synaptic complexes of XerCD, where previous single-molecule work has only dealt with unsynapsed XerCD-dif (32).…”
mentioning
confidence: 99%
“…Previous studies of FtsK C assembly and translocation have used biochemical methods (26,27) and single-molecule techniques, including magnetic and optical tweezers (18,(28)(29)(30); tethered particle motion (TPM) (18); and, more recently, DNA curtains (31,32). Optical/magnetic tweezers and TPM experiments have relied on loop extrusion by FtsK C to observe its action (looping by FtsK shortens the length between two DNA ends, hence displacing the bead used in TPM or optical/magnetic tweezers).…”
mentioning
confidence: 99%